Congenital short bowel syndrome: a case report and review of the literature - E. Yu. Dyakonova; A. S. Gurskaya; O. N. Nakovkin; K. A. Kazakova; M. A. Varichkina; N. V. Zhurkova; R. R. Baiazitov; D. M. Akhmedova; A. O. Tarzian; A. A. Shchukina (Вестник хирургии имени И.И. Грекова)
Congenital short bowel syndrome is a rare condition of the newborn, with several reports demonstrating high mortality. For the first time in Russia, we report a case of treatment of a newborn girl with genetically confirmed congenital short bowel syndrome, and also provide a review of the literature on this syndrome. After birth, the child experienced constant vomiting of bile with a progressive decrease in body weight. The laparotomy for congenital adhesions between the loops of the small intestine with severe violations of the evacuation function revealed that the small bowel was 50 cm in length, confirming the diagnosis of congenital short bowel syndrome. The genetic test, using whole exome sequencing, identified a homozygous mutation in the CLMP gene in this patient. A positive result in the postoperative period was achieved using the protocol for the management of patients with short bowel syndrome. Currently, the girl is 11 months old, body weight is 9 kg, development is harmonious. Long-term survival of children with congenital short bowel syndrome is now possible if enteral feeds are introduced early to promote intestinal adaptation, with subsequent weaning off parenteral nutrition.